Cryptosporidium and other intestinal parasitic infections among HIV patients in southern Ethiopia: significance of improved HIV-related care. Issue 1 (December 2016) - Shimelis, Techalew; Tassachew, Yayehyirad; Lambiyo, Tariku
Abstract Background Intestinal parasitic infections are known to cause gastroenteritis, leading to higher morbidity and mortality, particularly in people living with HIV/AIDS. This study aimed to determine the prevalence ofCryptosporidium and other intestinal parasitic infections among HIV patients receiving care at a hospital in Ethiopia where previous available baseline data helps assess if improved HIV-related care has reduced infection rates. Methods A cross-sectional study was conducted at Hawassa University Hospital in southern Ethiopia from May, 2013 to March, 2014. A consecutive sample of 491 HIV- infected patients with diarrhea or a CD4 T cell count < 200 cells/μl were prospectively studied. A single stool sample was collected from each study participant and processed using direct, formol-ether concentration, and modified Ziehl-Neelsen techniques for the diagnosis ofCryptosporidium and other intestinal parasites. The study was approved by the Institutional Review Board of the College of Medicine and Health Sciences, Hawassa University. Physicians managed participants found to be infected with any pathogenic intestinal parasite. Results The overall prevalence of intestinal parasitic infections among the study population was 35.8 %. The most prevalent parasites wereCryptosporidium (13.2 %), followed byEntamoeba histolytica/dispar (10.2 %), andGiardia lamblia (7.9 %). The rate of single and multiple infections were 25.5 and 10.3 %, respectively. Patients with a CD4 T cell count < 200 cells/μl had a similar rate of any intestinal parasitic infection or cryptosporidiosis compared to those with counts ≥ 200 cells/μl, but with some type of diarrhea. Conclusion The study shows high prevalence of intestinal parasitic infections in the study population. However, the results in the current report are significantly lower compared to previous findings in the same hospital. The observed lower infection rate is encouraging and supports the need to strengthen and sustain the existing intervention measures in order to further reduce intestinal parasitic infections in people living with HIV/AIDS.